HEPATOPROTECTIVE ACTIVITY STUDY OF PLANT POLYPHENOLS UNDER THE EXPERIMENTAL INSULIN RESISTANCE - Загайко, А.Л.; Красільнікова, О.А.; Кравченко, Г.Б.; Кочубей, Ю.І. (World of Medicine and Biology, 2016)
A perspective direction of modern pharmacology is the study of the biological activity of plant-derived substances. The aim of the work was to study the hepatoprotective activity of grapes polyphenol concentrate, quercetin and epigallocatechin gallate on lipid content in rat liver and activity of hepatospecific enzymes in the blood under the experimental insulin resistance (IR). Experiments were performed on male Wistar rats. IR was induced by high-fat, high-fructose diet (FD). Phospholipids (PL) level decrease and triacylglycerols (TAG), free fatty acids (FFA) and cholesterol (CH) levels increase were found in rat liver under FD. In the blood, alanine aminotransferase, aspartate aminotransferase and γ-glutamyl transepeptidase activity increase were shown. Plant polyphenols administration positively affect the liver lipid content in rats: PL level raise and TAG, FFA and CH levels reduction were found. Reducing the activity of hepatospecific enzymes in blood indicates plasma membrane normalization of liver cells. The most effective was the grape polyphenol concentrate. Thus, the plant polyphenols showed significant hepatoprotective effect, which is manifested in normalization of lipid levels in the liver and recovery the permeability of plasma membranes.
Keywords: vegetable field phenols; rats; fructose; lipids liver